Basic psychological needs as predictors of psychological well-being among teens selling farm products in Iloilo. - Nieves, Dani Gabrielle N.
Basic Psychological Needs Theory is one of the six-mini theories of Self-Determination Theory that proposes that the three psychological needs, when satisfied, can lead to a better psychological well-being. This study investigated the predictive variance of autonomy, competence and relatedness on psychological well-being. This research utilized a mixed method approach and was administered to adolescents, age 15-30, from 7 different markets in the Iloilo province, that are involved in selling vegetables and fruits (n=106). Linear regression analysis revealed that autonomy, competence and relatedness showed significant variance on psychological well-being. Hierarchical regression analysis showed that among the three needs, autonomy is the greatest predictor of psychological well-being